1999
DOI: 10.1111/j.1472-8206.1999.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of methotrexate elimination after high dose infusion in children with acute lymphoblastic leukaemia using a population pharmacokinetic approach

Abstract: High-dose methotrexate (HD-MTX) with leucovorin rescue is a component of therapy in children with acute lymphoblastic leukaemia. Since MTX toxicity is related to drug exposure, a monitoring of serum MTX concentrations at H24, H48, H72 and until the concentration is less than 0.2 micromol/L is commonly performed. However, a number of patients may reach concentrations of less than 0.2 micromol/L long before the next sampling is scheduled. The aim of our study was to develop a Bayesian method predicting the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 27 publications
(4 reference statements)
4
35
2
Order By: Relevance
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 84%
“…The former was the combination that had the weakest correlations in the present study, and the latter was the most frequently reported combination in previous studies. [9][10][11][12][13][14][15][16][17][18][19] As shown above, the sum of the absolute value of correlation coefficients among V 1 , k 10 , k 12 , and k 21 was 1.05 for regimen B, whereas V 1 , V 2 , CL, and Q was 3.29 for regimen B. Because of the relatively strong correlations among V 1 , V 2 , CL, and Q, this combination of the population parameters was considered to be a good target for a comparison with V 1 , k 10 , k 12 , and k 21 .…”
Section: Evaluation Of the Effect Of Correlations Among Population Pamentioning
confidence: 99%
See 3 more Smart Citations